Survey and detection for citrus tristeza virus in Florida groves with an unconventional tool: The Asian citrus psyllid - Britt-Ugartemendia, Kellee; Turner, Donielle; Sieburth, Peggy; Batuman, Ozgur; Levy, Amit (Frontiers in Plant Science, 2022)
The citrus industry of Florida faces insurmountable challenges against the destructive diseases citrus tristeza and Huanglongbing (HLB, or citrus greening). Though the tristeza causal agent, citrus tristeza virus (CTV), has been in Florida decades longer than HLB, growers have concentrated most of their efforts on combating the more detrimental HLB. The Asian citrus psyllid (Diaphorina citri; ACP) is the insect vector of the bacterial pathogen Candidatus Liberibacter asiaticus and transmits the incurable HLB to all commercial citrus. During our searches for biological and viral controls against the ACP, we consistently detected sequences of CTV in Florida field populations of ACP. This unexpected finding led us to investigate whether ACPs collected from young shoots could be used as a tool to survey CTV in Florida citrus groves. We first surveyed the most common CTV strains in Florida (T30, T36, and VT/T68) in citrus trees on mostly sour orange (Citrus aurantium) rootstock, the rootstock susceptible to CTV decline. Out of 398 trees sampled across four years (2018-2022), approximately 18% were positive for CTV, with more than half of the CTV-positive trees infected with strain T30. Simultaneously, we looked at CTV strains in ACPs during this time and found that approximately 88% of pooled adult and nymph ACPs also had CTV, with over half the positive samples having the T36 strain. As a result of the much higher CTV incidences in the ACPs, we conducted a second investigation into whether we could more easily detect the same CTV strains in ACP nymphs as in CTV-infected citrus tissue. After individually sampling 43 trees and pooling the nymphs from each tree, we detected CTV at about the same incidence in the citrus tissue and the nymphs, but with much less ACP tissue, time, and resources required for detection compared to citrus tissue. Results from this study illustrate the sustained threat of CTV to Florida citrus and demonstrate the ACP as a potential bioindicator for CTV.